2021
DOI: 10.1128/jb.00630-20
|View full text |Cite
|
Sign up to set email alerts
|

Genome Copy Number Regulates Inclusion Expansion, Septation, and Infectious Developmental Form Conversion in Chlamydia trachomatis

Abstract: DNA replication is essential for the growth and development of Chlamydia trachomatis, however it is unclear how this process contributes to and is controlled by the pathogen’s biphasic lifecycle. While inhibitors of transcription, translation, cell division, and glucose-6-phosphate transport all negatively affect chlamydial intracellular development, the effects of directly inhibiting DNA polymerase have never been examined. We isolated a temperature sensitive dnaE mutant (dnaEts) that exhibits a ∼100-fold red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Detailed quantitative and volumetric analyses have shown a tight correlation between chlamydial number and inclusion size over the entire course of a wild-type infection ( 13 ). Similarly, a correlation between chlamydial genome copy number and inclusion growth has been reported ( 14 ). As inclusion size can be readily monitored by immunofluorescence microscopy, it has often been used as a surrogate measure for the overall infection.…”
Section: Introductionmentioning
confidence: 68%
“…Detailed quantitative and volumetric analyses have shown a tight correlation between chlamydial number and inclusion size over the entire course of a wild-type infection ( 13 ). Similarly, a correlation between chlamydial genome copy number and inclusion growth has been reported ( 14 ). As inclusion size can be readily monitored by immunofluorescence microscopy, it has often been used as a surrogate measure for the overall infection.…”
Section: Introductionmentioning
confidence: 68%
“…It is in these inclusions that C. trachomatis transform into reticulate bodies and replicate by binary fission -the second phase of C. trachomatis life cycle. In this stage, C. trachomatis utilizes nutrients and adenosine triphosphate from the host cytoplasm, and when these resources run out, the reticulate bodies transform back into elementary bodies and are secreted into the extracellular environment to infect neighboring cells [12].…”
Section: Trachomatis Life Cyclementioning
confidence: 99%
“…Another study has reported that C. trachomatis RBs undergo cell size reduction prior to differentiating into their non-replicative, infectious forms ( Lee et al, 2018 ), effectively linking the processes of cell size regulation, division, and differentiation. The processes of DNA replication and septation are decoupled in C. trachomatis ( Lambden et al, 2006 ); however, the inhibition of replication has been shown to directly affect PG septal formation ( Brothwell et al, 2021 ). The exact mechanism by which RBs regulate their division process and by proxy their cell size, remains unknown.…”
Section: Introductionmentioning
confidence: 99%